Norman Lewis Corwin papers - Corwin, Norman, 1910-2011.
Autograph draft and corrected typescripts of Corwin's 1941 radio broadcast "We Hold These Truths." Also includes "An American in England," a series of plays given over the Columbia Network from New York City in December 1942.
Dramatist.
Collection material in English.
Keywords: Radio programs; Radio scripts; Columbia Broadcasting System, inc; Dramatists